Serbia: Challenges for Monetary Policy During the Transition Period - Popović, Dušan V. (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The National Bank of Serbia, acting as a central bank, was established as an independent and autonomous institution accountable for its work in the National Assembly of the Republic of Serbia. The status, organisation, mandate, and functions of the central bank, as well as its relations with other national and international institutions, are regulated by the Constitution of the Republic of Serbia, the Act on the National Bank of Serbia, and the Statute. The National Bank of Serbia has engaged in longstanding cooperation with the European Central Bank. Over the last 20 years, the two authorities have conducted numerous cooperation projects and (in 2018) signed a memorandum of understanding. Since 2014, the National Bank of Serbia and the European Central Bank have held regular annual bilateral meetings. In addition to capacity-building cooperation agreements, the two authorities signed the Agreement on Cooperation in the area of preventing counterfeiting and detecting counterfeit euro banknotes in Serbia. Based on this agreement, the European Central Bank will deliver the technical specifications of the original euro banknotes and the classification of counterfeits to the Serbian central bank. The main challenge faced by the national authorities in recent years has been the COVID-19 crisis. Both the National Bank of Serbia and the Government undertook measures in response to the COVID-19 pandemic. The central bank’s measures consist of monetary policy and a moratorium on debt payments. In addition, the Government of Serbia adopted the Program of Economic Measures to reduce the negative effects caused by the coronavirus pandemic and support the Serbian economy. The programme included tax policy measures, direct assistance to the private sector, measures to preserve liquidity in the private sector, and other measures. Notably, the COVID-19 crisis was complemented by an energy crisis, which was further highlighted by recent geopolitical developments. Keywords: monetary policy, Serbia, European integration, central bank, convergence